A 15‐year follow‐up study of radiofrequency catheter ablation for atrial fibrillation in patients with tachycardia‐bradycardia syndrome. (21st July 2022) - Tokuda, Michifumi; Yamashita, Seigo; Hachisuka, Eri; Sato, Hidenori; Oseto, Hirotsuna; Yokoyama, Masaaki; Tokutake, Kenichi; Yokoyama, Kenichi; Kato, Mika; Narui, Ryohsuke; Tanigawa, Shinichi; Yoshimura, Michihiro; et al.
Abstract: Introduction: Catheter ablation for atrial fibrillation (AF) in patients with tachycardia‐bradycardia syndrome (TBS) can be a major therapeutic option to replace permanent pacemaker implantation (PMI). However, the very long‐term outcome of more than 15 years in these patients has not been elucidated. Methods: From 2002 to 2008, 25 consecutive TBS patients (62 ± 7.9 years old, 68% male) with both AF and symptomatic sinus pauses (>3.0 s) were performed radiofrequency AF ablation. These patients were followed for 15 ± 2.7 years. Results: The median longest sinus pause before the ablation procedure was 6.0 s (4.4–8.0). Following 1.6± 0.8 ablation procedures, 18 (72%) patients remained free from AF. Three (12%) patients died due to noncardiovascular causes, and seven (28%) patients underwent PMI due to symptomatic sinus pause after recurrent AF in five patients and progression of sinus node dysfunction in two patients. The median duration from the first AF ablation to PMI was 6.3 years (range: 9 days to 11.0 years). Five and two patients required PMI more than 5 and 10 years after the first ablation procedure, respectively. Conclusion: AF ablation prevented PMI in 72% of TBS patients for a 15‐year follow‐up. However, in consideration of the long duration of PMI, a continuous careful long‐term follow‐up was warranted.